2015
DOI: 10.1007/s10611-015-9561-y
|View full text |Cite
|
Sign up to set email alerts
|

Women in prison: unhealthy lives and denied well-being between loneliness and seclusion

Abstract: The purpose of this study is to investigate the well-being of female inmates in Italian prisons. The hypothesis is that stress in women prisoners is strictly related both to "external" networks and "internal" support, and is more linked to the feeling of loneliness than to coping with the difficulties of prison life. Qualitative study involving adult female prisoners in the prisons of three Italian regions (Campania, Lazio, Emilia Romagna). 37 individual semi-structured interviews were conducted. The interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…All types of leisure present psychological benefits. Women experience solitude as a disease: access to social activities, work, and projects help keep depression at bay (Esposito 2015). Other benefits include reduced stress, anxiety, aggression, or other negative emotions, as well as increased self-esteem, concentration, pleasure, well-being, self-reflection, relaxation, peacefulness, connection with emotions, and positive outlook on the future (Davila Pedlar, Yuen, and Fortune 2008;Twaddle et al 2007;Leeder and Wimmer 2007).…”
Section: Individual Benefits and Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…All types of leisure present psychological benefits. Women experience solitude as a disease: access to social activities, work, and projects help keep depression at bay (Esposito 2015). Other benefits include reduced stress, anxiety, aggression, or other negative emotions, as well as increased self-esteem, concentration, pleasure, well-being, self-reflection, relaxation, peacefulness, connection with emotions, and positive outlook on the future (Davila Pedlar, Yuen, and Fortune 2008;Twaddle et al 2007;Leeder and Wimmer 2007).…”
Section: Individual Benefits and Issuesmentioning
confidence: 99%
“…Leisure functioning in educational programs is tied to readiness for returning to society, specifically through perception of freedom and motivation in leisure (Link and Williams 2017). Skills acquired through leisure and programs could affect one's criminal identity and help one adopt a more conventional lifestyle, which in turn may reduce or prevent reoffending (Esposito 2015;Fortune et al 2010;Johnson 2008;Kendall 1993;Link and Williams 2017;Meek and Lewis 2014;Ozano 2008;Pedlar, Yuen, and Fortune 2008;Pedlar, Arai, and Yuen 2007;Sempé et al 2006;Yuen 2011;Yuen and Pedlar 2009;Nugent and Loucks 2011;Johnson 2008). However, these results must be nuanced as all of these studies occurred while individuals were still incarcerated; they thus speak to anticipated rehabilitation, reintegration, or non recidivism.…”
Section: Individual Benefits and Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Leisure functioning in educational programs is tied to readiness for returning to society, specifically through perception of freedom and motivation in leisure (Link and Williams, 2017). Skills acquired through leisure and programs could affect one's criminal identity and help one adopt a more conventional lifestyle, which in turn may reduce or prevent reoffending (Kendall, 1993;Sempé et al, 2006;Pedlar et al, 2007Pedlar et al, , 2008Johnson, 2008;Ozano, 2008;Yuen and Pedlar, 2009;Fortune et al, 2010;Nugent and Loucks, 2011;Yuen, 2011;Meek and Lewis, 2014;Esposito, 2015;Link and Williams, 2017). However, these results must be nuanced as all of these studies occurred while individuals were still incarcerated; they thus speak to anticipated rehabilitation, reintegration, or non-recidivism.…”
Section: Leisure Practices As Participating In Prison's Missions Indimentioning
confidence: 99%
“…Loneliness is one of the most important factors affecting the emotional state of prisoners. Indeed, one study found that loneliness is more important to prisoners than coping with the difficulties of prison life (Esposito, 2015). Furthermore, the number of prisoners' friends made a difference in loneliness (Desmond, 1991), and the lower the loneliness, the less depressed mood (Merten, Bishop, & Williams, 2012).…”
Section: Introductionmentioning
confidence: 99%